Spike-timing-dependent plasticity offers delay-gated oscillatory potentiation for autaptic weights - Onda, Risa; Ishida, Mihoko; Hattori, Kouhei; Yamamoto, Hideaki; Tanii, Takashi (Frontiers in Neural Circuits, 2025)
Neuronal networks in animal brains are considered to realize specific filter functions through the precise configuration of synaptic weights, which are autonomously regulated without external supervision. In this study, we employ a single Hodgkin–Huxley-type neuron with autapses as a minimum model to computationally investigate how spike-timing-dependent plasticity (STDP) adjusts synaptic weights through recurrent feedback. The results show that the weights undergo oscillatory potentiation or depression with respect to autaptic delay and high-frequency stimulation. Our findings suggest that the STDP-mediated modulation of autaptic weights, governed by autaptic delay and input frequency, may serve as a mechanism for promoting network-level synchronization in neural systems if the network contains neurons with autapses.